1997
DOI: 10.1111/j.1365-2621.1997.tb12241.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat Curing of Whey Protein Films

Abstract: Heat curing of edible whey protein isolate (WPI) films was studied as a means of improving mechanical and water vapor barrier properties. Curing temperature and relative humidity (RH) effects on the rate of change of maximum tensile stress (TS), elongation at break (E), Young's Modulus (Y m ), and water vapor permeability (WVP) were investigated. Cure time linearly affected TS and Y m , while influencing E and WVP exponentially. Increased cure temperature and reduced RH accelerated TS increase, E and Y m decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 18 publications
4
30
1
1
Order By: Relevance
“…The reason may have been that our curing chamber was a closed system with no air circulation. Similar to the results of our study, increases in film TS and decreases in film E also were observed for whey protein films heat-treated at 60, 70, or 80 °C (Miller et al, 1997), wheat gluten films thermally-treated at 65, 80, or 95 °C (25), and SPI films heat treated at 80, 90, or 95 °C (Gennadios et al, 1996;Rhin et al, 2000). Miller and others (1997) reported that curing temperature and RH affected the rate of change of maximum TS, E, Young's modulus (Y m ), and WVP of whey protein films.…”
Section: Tensile Strength and Elongationsupporting
confidence: 79%
See 1 more Smart Citation
“…The reason may have been that our curing chamber was a closed system with no air circulation. Similar to the results of our study, increases in film TS and decreases in film E also were observed for whey protein films heat-treated at 60, 70, or 80 °C (Miller et al, 1997), wheat gluten films thermally-treated at 65, 80, or 95 °C (25), and SPI films heat treated at 80, 90, or 95 °C (Gennadios et al, 1996;Rhin et al, 2000). Miller and others (1997) reported that curing temperature and RH affected the rate of change of maximum TS, E, Young's modulus (Y m ), and WVP of whey protein films.…”
Section: Tensile Strength and Elongationsupporting
confidence: 79%
“…Pérez-Gago and others (1999) reported that heat-denatured whey protein films had higher tensile properties than native whey protein films. Studies showed that heat curing improved the mechanical toughness and moisture resistance of cast protein films made from corn zein (Julius, 1967), wheat gluten (Kolster et al, 1992;Ali et al, 1997), collagen (Weadock et al, 1984), whey protein (Miller et al, 1997), and soy protein (Gennadios et al, 1996;Rangavajhyala et al, 1997;Rhim et al, 2000). These results suggest that covalent cross-linking, caused by heat denaturation of protein, is responsible for film water insolubility and higher tensile properties.…”
Section: Introductionmentioning
confidence: 82%
“…On the other hand, DE values of the films stored at 35 and 45°C gradually increased over time. The discoloration of WPI-based films at elevated temperatures was reported to mainly associate with Maillard browning of whey proteins and traces of reducing sugars (Miller et al 1997;Trezza and Krochta 2000). Nonetheless, DE values of all stored films were below 6, the threshold value detectable by the human eye (Garcia and Sobral 2005).…”
Section: Changes In Properties Of Spiced Film During Storagementioning
confidence: 97%
“…As proteínas são biopolímeros formados por 20 tipos de monômeros (aminoácidos) diferentes, cuja estrutura é determinada pela composição e seqüência desses aminoácidos, e conseqüentemente, pelas interações inter e intramoleculares que podem ocorrer através dos resíduos das cadeias laterais polares e não polares [7]. Dessas características estruturais e a composição quí-mica do polímero dependem também, as propriedades funcionais das proteínas, incluindo as propriedades filmogênicas [8,20,26]. Essas propriedades podem ser modificadas em função do pH, tratamento térmico e de aditivos [15].…”
unclassified